Study on the mechanism of Shuanghe decoction against steroid-induced osteonecrosis of the femoral head: insights from network pharmacology, metabolomics, and gut microbiota - Kai Zhu; Wanxin Liu; Yuanyuan Peng; Xiaoqiang Wang; Zhenhao Wang; Jun Zheng; Guoying Deng; Qiugen Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Steroid-induced osteonecrosis of the femoral head (SONFH) is a challenging and debilitating orthopedic condition with a rising incidence in recent years. Shuanghe Decoction (SHD), a traditional Chinese medicine formula, has shown significant efficacy in treating SONFH, though its underlying mechanisms remain unclear. Purpose This study aims to elucidate the therapeutic effects and potential mechanisms of SHD on SONFH through in vivo experiments, combined with network pharmacology, metabolomics, and gut microbiota analysis. Materials and methods Forty male Sprague-Dawley rats (300 ± 20 g) were randomly assigned to four groups: Control, Model, SHD-L, and SHD-H, with 10 rats each. SONFH was induced in all groups except the Control group using lipopolysaccharide and methylprednisolone. The SHD-L and SHD-H groups were treated with Shuanghe decoction at doses of 4.86 g/kg/day and 9.72 g/kg/day, respectively, for eight weeks. Bone morphology, pathological changes, and osteogenic factors were evaluated using Micro-CT, histological staining, and immunohistochemistry. Network pharmacology, metabolomics, and gut microbiota analyses were conducted to explore SHD’s mechanisms. Results SHD improved bone morphology and increased osteogenic factor expression (RUNX2, OCN, COL-I). Network pharmacology indicated that metabolic pathways play a key role in SHD’s therapeutic effects. Metabolomic analysis identified 14 differential metabolites, including 21-hydroxypregnenolone and tyramine, which were restored to normal levels by SHD. Gut microbiota analysis revealed that SHD modulated bacterial abundance, particularly Verrucomicrobia, Allobaculum, and Burkholderiales. A comprehensive network identified two key metabolites (tyramine, 21-hydroxypregnenolone), seven targets (CYP19A1, CYP1A2, CYP1B1, CYP2C9, CYP3A4, MIF, and HSD11B1), two metabolic pathways (tyrosine metabolism, steroid hormone biosynthesis), and four bacterial taxa (Jeotgalicoccus, Clostridium, Corynebacterium, rc4-4) as central to SHD against SONFH. Conclusion SHD alleviates SONFH by reshaping gut microbiota, reversing metabolic imbalances, and enhancing osteogenesis. Our findings provide novel insights into the pharmacological mechanisms of SHD, laying a foundation for its clinical application in treating SONFH. Graphical Abstract